A Mean‐Field Model for Oxygen Reduction Electrocatalytic Activity on High‐Entropy Alloys. Issue 18 (11th August 2022) - Pedersen, Jack K.; Clausen, Christian M.; Skjegstad, Lars Erik J.; Rossmeisl, Jan
Abstract: High‐entropy alloys (HEAs) represent near‐equimolar points in the middle of a vast composition space of multi‐metallic catalysts. Successful modeling of the catalytic activity of these complex materials allows to search this composition space for optimal catalysts. This study shows the effect of approximating the ligand effect of the surrounding atoms around an adsorption site with a mean‐field perturbation. Modeling the electrocatalytic activity of the oxygen reduction reaction on the quinary AgIrPdPtRu HEA, it is shown that the extent of such a mean‐field approximation is valid up to and including equimolar ternary alloys, corresponding to 60.3 % of the quinary composition space, by comparing to models that consider the ligand effect locally. When extrapolating to make predictions far from near‐equimolar compositions, such as for binary alloys, the mean field has been sufficiently perturbed to cause large discrepancies. Here, the local ligand models thus prove more useful for discovering optimal catalysts. Abstract : High‐entropy alloys : This study investigates whether approximating the adsorption energy distributions of Ag‐Ir‐Pd‐Pt‐Ru high‐entropy alloy with normal distributions is a valid approximation for prediction of catalytic activities for the electrochemical oxygen reduction reaction.